Preparation, characterization, and dynamic adsorption–desorption studies on polypyrrole encapsulated TiO2 nanoparticles. Issue 20 (8th February 2016) - Sultan, Adil; Anwer, Tarique; Ahmad, Sharique; Mohammad, Faiz
ABSTRACT: Binary doped polypyrrole (PPy) encapsulated Titania (TiO2 ) nanoparticles were prepared by oxidative polymerization using FeCl3 as oxidant in presence of camphorsulfonic acid (CSA) as surfactant. Both FeCl3 (oxidant) and camphorsulfonic acid (surfactant) also act as dopant and hence thus prepared polypyrrole/Titania (TiO2 @PPy) is termed as binary doped nanocomposite i.e. FeCl3 dopes polypyrrole by oxidation mechanism while camphorsulfonic acid dopes polypyrrole by protonic doping mechanism. The TiO2 @PPy coreshell nanocomposites were characterized by Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD), thermogravimetry, differential scanning calorimetry (DSC), field emission‐scanning electron microscopy (FE‐SEM), and inductance‐capacitance‐resistance (LCR) measurements. The results indicated that the structural and electrical properties of the TiO2 @PPy coreshell nanocomposites were significantly influenced by the extent of TiO2 nanoparticles loading of polypyrrole. The direct current (DC) electrical conductivity of the as‐prepared TiO2 @PPy coreshell nanocomposites was higher than that of PPy. As‐prepared TiO2 @PPy coreshell nanocomposites were also studied for their dielectric losses for alternating current (AC) which is useful characteristic for their application in the fabrication of charge storing devices. TiO2 @PPy coreshell nanocomposites showed synergistic effect of combining components in improving their alcohol sensing properties. This improvement may be attributed to the adsorption on and desorption from alcohols TiO2 @PPy interface of the nanocomposites and alcohol vapors causing decrease in depletion region. The TiO2 @PPy coreshell nanocomposites were observed to show better reproducibility of electrical conductivity and fast self‐recovery during the alcohol vapor sensing process. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43411. Abstract :